PENGARUH CURRENT RATIO (CR) DAN DEBT TO EQUITY RATIO (DER) TERHADAP RETURN ON ASSET (ROA) PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Agus Firmansyah; Ihwan Satria Lesmana (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2021)
The return on asset value is one of the considerations that influence investors to invest in a company. The higher the return on asset, the more invested. There are several ratios that affect considerations in investing investors, including current ratio and debt to equity ratio. This study aims to determine the effect of current ratio and  debt to equity ratio on return on assets in pharmaceutical sub-sector manufacturing companies listed in IDX for the period 2015-2019. The method in this study uses quantitative method, the population in this study there are 10 pharmaceutical companies and samples used by 8 pharmaceutical companies registered in IDX witha period of cussingduring2015-2019. The results showed that partially variable  there is an influence of current ratio to return on asset, there is a negative influence of debt   to equity ratio to return on asset.